1981
DOI: 10.1093/jn/111.2.391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin B-6 Deficiency and 4′-Deoxypyridoxine on Pyridoxal Phosphate Concentrations, Pyridoxine Kinase and Other Aspects of Metabolism in the Rat

Abstract: Male rats about 100 days old were fed a B-6 deficient diet supplemented with 4'-deoxypyridoxine (1 g/kg diet) and/or pyridoxine hydrochloride (22 mg/kg diet) for 30 to 35 days. Addition of 4'-deoxypyridoxine to the B-6-deficient diet produced greater losses in body weight (P less than 0.05) and thymus weight (P less than 0.01) than in B-6-deficient pair-fed controls. 4'-Deoxypyridoxine combined with a B-6-deficient diet produced no decreases in the concentration of pyridoxal phosphate or pyridoxine kinase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

1982
1982
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
7
0
5
Order By: Relevance
“…Given that the inclusion of 1ADP in the CD diet had no impact on performance of the rats is strong evidence that the toxicological effects of 1ADP were due to its impact on B 6 status. Furthermore, prior studies have demonstrated that reductions in weight gain and FER elicited by anti-pyridoxine compounds were not solely the effect of reduced intake but rather due to the metabolic insults on amino acid, carbohydrate and lipid metabolism [37,39]. Clearly, those rats consuming adequate vitamin B 6 are generally protected from the oral exposure to 1ADP, at least as it pertains to growth and feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the inclusion of 1ADP in the CD diet had no impact on performance of the rats is strong evidence that the toxicological effects of 1ADP were due to its impact on B 6 status. Furthermore, prior studies have demonstrated that reductions in weight gain and FER elicited by anti-pyridoxine compounds were not solely the effect of reduced intake but rather due to the metabolic insults on amino acid, carbohydrate and lipid metabolism [37,39]. Clearly, those rats consuming adequate vitamin B 6 are generally protected from the oral exposure to 1ADP, at least as it pertains to growth and feed intake.…”
Section: Discussionmentioning
confidence: 99%
“…Van den Berg et al (1982) also reported that the contents of pyridoxal 5-phosphate in rat liver and plasma were dependent on the amount of pyridoxine in the diet. In vitamin B-6deficient rat liver, the activity of pyridoxal kinase as well as the content of pyridoxal 5-phosphate were decreased (Meisler & Thanassi, 1980;Coburn et al, 1981). Pyridoxamine 5-phosphate oxidase activity in rat fed on a pyridoxine-deficient diet was not different from controls (Rasmussen et al, 1979;Meisler & Thanassi, 1980).…”
Section: Discussionmentioning
confidence: 90%
“…It can be phosphorylated by pyridoxal kinase to form deoxypyridoxal phosphate, which inhibits pyridoxal-phosphate-requiring enzymes. Cobum et al [3] reported that addition of deoxypyridoxine to a vitamin-B6-dcficicnt diet produced no further decrease in pyridoxal phosphate concentration and pyri doxal kinase activity in tissues compared with the control. It has also been reported that the effects of deoxypyridoxine on taurine metabolism [9], glycine metabolism [10] and liver aminotransferase activity [2] differ from those of dietary vitamin Bö deficiency.…”
Section: Discussionmentioning
confidence: 99%